Validity of booklet results of characterization of morphology and anatomy of mentawa plants based on local wisdom in Dusun Timur District - Rahma Salsabila; Ita Ita; Istiqamah Istiqamah (Practice of The Science of Teaching Journal: Jurnal Praktisi Pendidikan, 2024)
The lack of reference sources that discuss the characterization of plant morphology and anatomy is a challenge in the development of effective learning resources. So it is one of the factors that encourages researchers to develop learning resources in the form of booklets. The booklet is comprehensively prepared but the appearance is still simple, so that in its use it is expected to help students in learning important aspects of plant morphology and anatomy to be more optimal. This study aims to describe the validity of the booklet resulting from the characterization of the morphology and anatomy of the mentawa plant based on local wisdom in East Dusun District. This study uses the Educational Design Research (EDR) research method with Tessmer's formative evaluation design and the research is limited to the one-to-one test stage. The results of the percentage of the booklet validity test by material experts were obtained with a score of 83.73% with a valid category, while the results of the percentage of the booklet validity test by media experts were obtained with ascore of 87.15% with a very valid category. Based on this, the booklet developed is declared valid and can be used as a learning resource based on local wisdom that is effective in improving student understanding, especially in morphology and plant anatomy courses. This research contributes to the development of learning media that is contextual and in accordance with local needs. Abstrak. Minimnya sumber referensi yang membahas karakterisasi morfologi dan anatomi tumbuhan menjadi tantangan dalam pengembangan sumber belajar yang efektif. Sehingga menjadi salah satu faktor yang mendorong peneliti untuk mengembangkan sumber belajar berbentuk buklet. Buklet disusun secara komprehensif namun tampilannya tetap sederhana, sehingga dalam penggunaanya diharapkan dapat membantu mahasiswa dalam mempelajari aspek penting dari morfologi dan anatomi tumbuhan agar lebih optimal. Penelitian ini bertujuan untuk mendeskripsikan validitas buklet hasil karakterisasi morfologi dan anatomi tumbuhan mentawa berbasis kearifan lokal di Kecamatan Dusun Timur. Penelitian ini menggunakan metode penelitian Educational Design Research (EDR) dengan desain evaluasi formatif Tessmer dan penelitian dibatasi sampai tahap uji perorangan (one-to-one). Hasil presentase uji validitas buklet oleh ahli materi didapatkan skor 83,73% dengan kategori valid, sedangkan hasil presentase uji validitas buklet oleh ahli media didapatkan skor 87,15% dengan kategori sangat valid. Berdasarkan hal tersebut maka buklet yang dikembangkan dinyatakan valid dan dapat digunakan sebagai sumber belajar berbasis kearifan lokal yang efektif dalam meningkatkan pemahaman mahasiswa, khususnya pada mata kuliah morfologi dan anatomi tumbuhan. Penelitian ini memberikan kontribusi dalam pengembangan media pembelajaran yang kontekstual dan sesuai dengan kebutuhan lokal.